A critical look at Romanesque sculpture in Maastricht (Bulletin KNOB, 2020)
The Romanesque sculpture in Maastricht, particularly in the St.-Servaas church and the O.L.Vrouwekerk (Our Lady's church), has been extensively and learnedly discussed by Elizabeth den Hartog. At first iconological and iconographical problems are dealt with. Against the background of historical and political developments Den Hartog has drawn conclusions that are not always shared by the reviewer. He makes critical comments on Den Hartog's interpretations and sometimes suggests different solutions. He also manages to supplement Den Hartog's line of reasoning by pointing to other monuments that may sometimes shed new light on various problems brought up in the publication.As regards capital no. 26 (St.-Servaas) the reviewer points to a relief in the Munster of Basel on which master builder and magister operis are praised as 'living stones'. The scenes on the 34 capitals in the imperial room (St.-Servaas) are convincingly interpreted as references to the battle between earthly sinners and the prospect of Heavenly Jerusalem.In some cases some scene or other should be 'read' differently from what Den Hartog proposes. The author dates the capitals in the ambulatory of O.L.Vrouwekerk earlier (1150-1160) than usual so far (1160-1167 by Bosman). According to Den Hartog this may reflect the failed Second Crusade - a pessimistic picture, as it were, in which anti-Semitic resentments are also expressed. The reviewer cannot quite follow her in this respect, because he does not always consider Den Hartog's line of reasoning convincing.